Humans Dominate the Social Interaction Networks of Urban Free-Ranging Dogs in India - Bhattacharjee, Debottam; Bhadra, Anindita (Frontiers in Psychology, 2020)
Research on human-animal interaction has skyrocketed in the last decade. Rapid urbanization has led scientists to investigate its impact on several species living in the vicinity of humans. Domesticated dogs (Canis lupus familiaris) are one such species that interact with humans and are also called man’s best friend. However, when it comes to the free-ranging population of dogs, interactions become quite complicated. Unfortunately, studies regarding free-ranging dog-human interactions are limited even though the majority of the world’s dog population is free-ranging. In this study, we observed twelve groups of free-ranging dogs in their natural habitat, the streets. We divided the study areas into two zones, namely – intermediate and high flux, based on human activity or movement. Six groups from each of the zones were observed mostly during daytime. We used social network analysis (SNA) to explore the dog-dog (intraspecific) and dog-human (interspecific) interactions. It was surprising to observe higher instances of interspecific interactions than the intraspecific ones, irrespective of the zones. Humans, in significantly higher occasions, initiated both positive and negative interactions in comparison to dogs. Our findings conclude that humans are a crucial part of the interaction network of Indian free-ranging dogs.